RESIDUAL EFFECT IN FIELD OF IMIDACHLORPRID IN THE CONTROL OF THE PINE APHID (Cinara spp.), UNDER TWO MODALITIES OF APPLICATION IN THE NURSERY OF SEEDLINGS - FARIA, Álvaro Boson de Castro; SOUSA, Nilton José (Scientia Agraria, 2007)
The pine aphid (Cinara Curtis, 1835) was detected in Brazil in 1996 by researchers of Brazilian Agricultural Research Corporation. Attacks can cause many damages in recent planted seedlings. Control techniques and strategies should consider environmental, economical and social parameters, in the "Integrated Pest Management" context. The objective was to determine the viability utilization of the imidachlorprid molecule for protecting seedlings against pine aphid, using two different methods of application in the nursery of seedlings. The methodology consisted in a completely randomized design, with three treatments (imidachlorprid in the watering form; imidachlorprid associated to the soil conditioning gel; Control group) and six repetitions. The infestation was evaluated through the parameters incidence and prevalence. The residual effect of imidachlorprid application on seedlings in nursery (watering form and associated to the conditioning soil gel), is prolonged for 80 days after the seedlings planting. This effect does not impede the initial infestation, however is capable to avoid the population expansion of the colonies.